Graphene-Derived Materials Interfacing the Spinal Cord: Outstanding in Vitro and in Vivo Findings - Domínguez-Bajo, Ana; González-Mayorga, Ankor; López-Dolado, Elisa; Serrano, María C. (Frontiers in Systems Neuroscience, 2017)
The attractiveness of graphene-derived materials (GDMs) for neural applications has fueled their exploration as components of biomaterial interfaces contacting the brain and the spinal cord. In the last years, an increasing body of work has been published on the ability of these materials to create biocompatible and biofunctional substrates able to promote the growth and activity of neural cells in vitro and positively interact with neural tissues when implanted in vivo. Encouraging results in the central nervous tissue might impulse the study of GDMs towards preclinical arena. In this mini-review, we revise the most relevant literature on the interaction of GDMs with the spinal cord. Studies involving the implantation of these materials in vivo in the injured spinal cord are first discussed, followed by models with spinal cord slides ex vivo and a final description of selected results with neural cells in vitro. A closing debate of the major conclusions of these results is presented to boost the investigation of GDMs in the field.